REPUBLIC OF KAZAKHSTAN IN COMBATING INTERNATIONAL TERRORIZM AND EXTREMISM - Bekbolatovna Байсагатова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article highlights the global structure for combating the financing of terrorism and extremism, the current realities show a steady trend of destructive terrorist devices to new alliances based intentions and develop new channels of financing. All this reinforces the search for effective mechanisms in the direction reliable counter their activities. The high level of threat to the existing reality of the world are forced to develop more new mechanisms of reaction, favoring the expansion and deepening of integration within both regional and global organizations.